Carotid artery thermography and infrared image processing with data management - Chin, Zheng Yang (2019)
Carotid artery stenosis, also known as carotid artery disease, is one of the common diseases that narrow the large neck arteries on both side of the neck which carry blood to human’s face and brain. Atherosclerosis is the main cause of carotid artery stenosis. Most of the people with carotid stenosis doesn’t have any symptoms until the clot form in the carotid artery or the artery is severely narrowed. Symptoms with first appear along with a mini-stroke, which is known as a transient ischemic attack. Transient ischemic attack is the consequence when blood flow to the brain is cut off for a short period of time and then restored. The symptoms of transient ischemic attack include numbness, have difficulty to talk and vision problems. Imaging methods can reveal evidence of mini-stroke, imaging tests that are able to diagnose and localize carotid artery include Dopper ultrasound test, Computed tomography angiography, Magnetic Resonance Angiography (MRA) and Cerebral Angiogram. The neck temperature distribution feature is one of the newly discovered parameters of diagnosis of carotid artery stenosis, and it can be displayed and recorded visually using Infrared thermography. Infrared thermography is an imaging technique that measures the radiation emanated from an object in the infrared range of the electromagnetic spectrum (9 - 13µm) and displays the result as an image of temperature distribution.[1] Since 90s era, with the breakthrough in infrared sensors, the advancement of infrared camera technology and the novel approaches of image post-processing algorithm, infrared thermography, is getting more and more attention in clinical medicine field.[2] Infrared thermography examines both spatial and temporal data relating to skin temperature. An acquisition of hundreds of consecutive high contrast transient images using an infrared thermal camera. The efficiency, safety and low cost of thermography make it a very useful auxiliary tool in diagnosing superficial diseases like vein thrombosis, muscular lesion, etc.[3] Since thermography is very responsive to any slight movement of subjects and involuntary body movements, such as cardiac motion and respiration which are inevitable, they will lead to movement artefacts (MAs), which will lead to deteriorating ii quality of produced images including blurring, ghosting and eventually undermining the accuracy of medical diagnosis. MAs will undermine the accuracy of the native temperature analysis as it will decrease the accuracy of temperature measurement between two specific points on the image. The project aims to develop a new clinical MA reduction post-processing algorithm in sequence of images with location algorithm based on edge distribution pattern. By introducing this new approach, we can extend the range of available methods for diagnosis in carotid artery stenosis.